Women's experiences of using the Alexander Technique in the postpartum: '…in a way, it's just as beneficial as sleep'. (December 2021) - Hanefeld, Nicola; Glover, Lesley; Jomeen, Julie; Wadephul, Franziska
Abstract: Background: The postpartum is a transitional period and potentially challenging time of heightened vulnerability for women where self-care is compromised. Mothers can ignore their needs while prioritising baby care. The Alexander Technique (AT) is a holistic self-management technique shown to be effective in managing some psycho-physical tension issues and heightening self-efficacy and self-care. The AT has potential to help compromised aspects of maternal well-being in the postpartum. Objective: To explore how women familiar with the AT use it for the key postpartum issues of Sleep and rest, one of three superordinate themes identified in a qualitative interview study. Design: Semi-structured interviews via Skype. Research approach: Interpretative Phenomenological Analysis. Participants: Seven women, with varying levels of AT experience, 4–13 months postpartum. Findings: Participants used a variety of self-care strategies through modifying their self-management with respect to Sleep and rest. Identified sub-themes were the 'knitting' of maternal and infant sleep, how participants rested using the AT and recognising maladaptive habits. Key conclusions: Further research into the AT as an approach to supporting perinatal well-being is warranted. Implications for practice: The AT has significance for self-management, self-care, addressing maternal needs for rest, restorative sleep as well as tension issues in the postpartum.